Euthanasia - at a moment of truth - Mufti, Tariq S. (Journal of Ayub Medical College Abbottabad, 2002)
A paraplegic infant due to meningomyelocele, a terminal cancer case in severe distress due to pains and a post traumatic comatose patient on life support equipment with minimal hopes of revival are some of the obvious examples in common medical practice today posing serious question of management plan specially regarding continuing efforts to sustain the life. The answer is not simple. All above like situations concerns whether or not a physician assists the patient for a merciful ending of the life to relieve him/her of sufferings and to cause a dignified death. EUTHANASIA is a term coined to do this job. This Greek word means ’˜ good death’. The practice of intentional mercy killing was customary in Greek and Roman times. In city of Sparta the newborns with sever birth defects and elderly were put to euthanasia. Most religions including, Islam, Christianity or Judaism prohibit intentional mercy killing (ACTIVE EUTHANASIA). However, in comatose patient with brain death the situation could be different. The patient may have short life if left alone or may carry on living for years if assisted with respirator etc. Many relatives insist to remove patient from life support equipment in this situation. This ’˜not doing something’ in preventing death is known as ’˜ PASSIVE EUTHANASIA’. In another scenario the physician is perplexed where for good reasons a person is asking for an assistance of some sort in causing euthanasia i.e. ’˜ VOLUNTARY EUTHANASIA’. There is only one state ’˜Oregon’ of USA in the world, which allows prescription but not actually administering lethal drug, on person’s request in certain medical situations. At present in United States and some other countries, under a legal Act, people make ’˜Living Wills’ in which they may give advanced directives allowing doctors for passive euthanasia. A recent development in this regard was witnessed in Holland where the court allowed euthanasia in a special case. Debating on the justification or otherwise of the Euthanasia is a complex issue involving legal, religious and cultural implications. Books on Jurisprudence mention it sparingly without coating any legal authority, but most probably the practice of passive euthanasia may be going on. Factual situation in our circumstances in the developing world (regarding passive euthanasia) is that the attendants willfully take a number of seriously ill patients away. The respirators are switched off on relative’s request or even on doctor’s decision. At times the only available life support equipment is transferred to another but better candidate for survival. Many patients cannot be facilitated to prolong their life because of non-availability of the equipment, expertise or funding etc. Finally terminal patients are commonly being used as donors for organ transplants, which is considered as a very noble cause. Answer to the question becomes still more difficult in view of the fact that medical science is progressing so fast that many of the conditions considered certainly fatal have become remediable. Relief of pain and symptoms of incurable disease are being made available. So, how to handle these situations is real dilemma. Recently in many of the developing countries including Pakistan the subject of the ethics for medical practitioners is being under popular discussion. Pakistan Medical & Dental Council is known to be in the process of preparing its current document in this regard. Guidelines are required addressing the issue specially considering the realities on ground.